Application of neural network on environmental impact assessment tools. (3rd July 2008) - Li, Jianzhi; Wu, Zhenhua; Zhang, Hong-Chao
Intended to provide an applicable evaluation methodology for product environmental impacts, this paper presents a survey of the current Environment Impact Assessment (EIA) methodologies. As a proposed remedy for existing tools, an Artificial Neural Network (ANN) approach is developed to estimate the missing data. To provide updated Life Cycle Assessment (LCA) information for major components used in the electronic industry, a detailed analysis of two recent delivered computer systems are provided in the paper using the ANN approach. This paper also discusses incorporation of recycling scenarios in the LCA for electronic products.